RISIKO K3 PADA PELAKSANAAN KONSTRUKSI BANGUNAN GEDUNG SWASTA - Ni Kadek Sri Ebtha Yuni; I Nyoman Suardika; I Wayan Sudiasa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Project risks sourced from the environment, planning, financial, technical, humane, criminal, and safety. The purpose of this study to identify the safety and health risks of building construction on structural and architectural work, determine the value of risk based on the results of identification, determine risk control based on the hierarchy of risk control. This research was conducted on a private construction project on structural and architectural work. The method used is interviews and surveys. Surveys were conducted to obtain risk identification, and interviews to respondents. There were 28 identified risks, 11 risks were in the mild category and 17 were moderate risks. This risks are controlled by tool box meetings, managing work positions, placement of materials and tools, installing signs, work permits, using helmets, shoes, safety belts, gloves, and masks.